2018
DOI: 10.1242/dev.161398
|View full text |Cite
|
Sign up to set email alerts
|

ANGUSTIFOLIA contributes to the regulation of three-dimensional morphogenesis in the liverwort Marchantia polymorpha

Abstract: mutants deficient in ANGUSTIFOLIA (AN) exhibit several phenotypes at the sporophyte stage, such as narrow and thicker leaves, trichomes with two branches, and twisted fruits. It is thought that these phenotypes are caused by abnormal arrangement of cortical microtubules (MTs). AN homologs are present in the genomes of diverse land plants, including the basal land plant , and their molecular functions have been shown to be evolutionarily conserved in terms of the ability to complement the mutation. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
2
23
0
1
Order By: Relevance
“…Complementation analyses confirmed that PpAN1‐1 and PpAN1‐2 functions are similar to those conserved in angiosperm AN s, because they rescued an‐1 phenotypes (Figure ). Past experiments with AN knockout mutants in A. thaliana and M. polymorpha have shown that deficient phenotypes only appeared in dominant generations: the gametophyte generation in M. polymorpha and the sporophyte generation in A. thaliana (Kim et al , ; Folkers et al , ; Furuya et al , ). Therefore, Furuya et al () assumed that ANs, involved in gametophyte morphogenesis in bryophytes were recruited for sporophyte morphogenesis in vascular plants during the evolution of land plants, specifically the transition in dominance from the gametophyte (haploid) to sporophyte (diploid) phases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Complementation analyses confirmed that PpAN1‐1 and PpAN1‐2 functions are similar to those conserved in angiosperm AN s, because they rescued an‐1 phenotypes (Figure ). Past experiments with AN knockout mutants in A. thaliana and M. polymorpha have shown that deficient phenotypes only appeared in dominant generations: the gametophyte generation in M. polymorpha and the sporophyte generation in A. thaliana (Kim et al , ; Folkers et al , ; Furuya et al , ). Therefore, Furuya et al () assumed that ANs, involved in gametophyte morphogenesis in bryophytes were recruited for sporophyte morphogenesis in vascular plants during the evolution of land plants, specifically the transition in dominance from the gametophyte (haploid) to sporophyte (diploid) phases.…”
Section: Discussionmentioning
confidence: 99%
“…The A. thaliana and M. polymorpha AN LOF mutants also showed similar phenotypes to the defects in cell expansion observed in P. patens . In A. thaliana an leaves, cell width expansion was reduced in epidermal and palisade tissue (Tsukaya et al , ; Hülskamp et al , ; Tsuge et al , ), whereas epidermal cell expansion was suppressed when Mpan knockout lines were cultured under conditions of enhanced thallus elongation (Furuya et al , ). Although an mutants in A. thaliana and M. polymorpha shared similar defects in cell expansion, effects on cortical MTs differed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell Phenotype Are Synergistically Enhanced in an-1 fugu5-1 ANGUSTIFOLIA (AN) is the sole homolog of CtBP/BARS in Arabidopsis. The CtBP/BARS protein family has diverse functions, intercellular localization, and developmental role in a wide range of land plants (Kim et al, 2002;Minamisawa et al, 2011;Furuya et al, 2018;Hashida et al, 2019). AN regulates the width of Arabidopsis leaves by controlling the polar elongation of leaf cells.…”
Section: Cotyledon Development and Pavementmentioning
confidence: 99%